Chemical Doping of the Organic Semiconductor C8‐BTBT‐C8 Using an Aqueous Iodine Solution for Device Mobility Enhancement. Issue 8 (12th February 2022) - Li, Jinghai; Babuji, Adara; Temiño, Inés; Salzillo, Tommaso; D'Amico, Francesco; Pfattner, Raphael; Ocal, Carmen; Barrena, Esther; Mas‐Torrent, Marta
Abstract: The performance of organic field‐effect transistors is still severely limited by factors such as contact resistance and charge trapping. Chemical doping is considered to be a promising key enabler for improving device performance, although there is a limited number of established doping protocols as well as a lack of understanding of the doping mechanisms. Here, a very simple doping methodology based on exposing an organic semiconductor thin film to an aqueous iodine solution is reported. The doped devices exhibit enhanced device mobility, which becomes channel‐length independent, a decreased threshold voltage and a reduction in the density of interfacial traps. The device OFF current is not altered, which is in agreement with the spectroscopic data that points out that no charge transfer processes are occurring. Kelvin probe force microscopy characterization of the devices under operando conditions unambiguously proves that an important reduction of the contact resistance takes place after their exposition to the iodine solution, reaching almost ohmic contact. Abstract : Thin films of the organic semiconductor C8‐BTBT‐C8 are doped following a very simple methology based on the exposure of the semiconductor to an aqueous iodine solution. This results in organic field‐effect transistors exhibiting a lower threshold voltage and a significantly improved mobility, which is caused by a dramatic decrease of the contact resistance.